Tratamento da Anemia ferropénica: Recomendações da Sociedade Portuguesa de Ginecologia - Águas,Fernanda (2019)
Overview and aims: This article addresses the diagnosis of anemia in the context of abnormal uterine bleeding and reviews the treatment options of iron deficiency anemia. This topic was worked out as a section of the Portuguese Consensus on Abnormal Uterine Bleeding, endorsed by the Portuguese Society of Gynaecology. The working group established recommendations that provide guidance to the medical society to better decision making concerning the treatment of iron deficiency anemia. We expose here evidence based guidelines consigning the diagnosis and management of this disease. Study design and Methods: A group of experts in the field performed a thorough systematic search of the publications on the treatment of iron deficiency anemia and a quality assessment of the included papers. On this basis a proposal was drawn up and later on was discussed and approved on consensus meeting with all members of the guidelines developing group reaching the final version of the recommendations. Conclusions: The present clinical practice guidelines on treatment of iron deficiency anemia may improve the diagnosis and management of this high prevalent disease.